Estimulación del desarrollo del lenguaje oral y su aporte en la fluidez verbal de los estudiantes de la escuela de educación básica “Balsalito”, Recinto las Mercedes, cantón Vinces, Provincia los Ríos. - Bustamante Santillán, Celso Inocencio (2017)
The investigative work that has been carried out is with the purpose of knowing the incidence of the stimulation of oral language development in the verbal fluency of the students of the basic school of Balsalito of the enclosure Las Mercedes in the canton Vinces, province of Los Ríos, starting from the premise that the students do not have good ability to read in a fluid way, which is due to a series of factors so that a fieldwork has been executed that allows to know the reality in the students of said institution Education about verbal fluency in their communications. With the use of different types of research it has been possible to study in a scientific way about the stimulation of oral language and the verbal fluency following concepts and ideas given by researchers and authors of different works both national and foreign, could also be used descriptive research In order to analyze in detail the different situations that are presented in the problematic that is being tried in order to have clear ideas that allow to propose a hypothesis that is verified with the use of statistical tools like the Chi Square test. The results of the research has made it possible to know that at present teachers do not have a comprehensive training in all subjects, so it is required that teachers are specialized in subjects to make the basic education process efficient, Trainings on a permanent basis to the teachers in different subjects so that they can have more information to carry out their work of educating the children.